2020
DOI: 10.1097/meg.0000000000001843
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic remission can be predicted by golimumab concentrations in patients with ulcerative colitis treated with the changed label

Abstract: Background In 2018, the European Medicines Agency (EMA) replaced a fixed 50 mg every 4-week maintenance regimen of golimumab for ulcerative colitis (UC) patients weighing <80 kg with new, flexible dosing that allows reactive dose optimization to 100 mg if clinically needed. We analyzed the endoscopic remission rates and pharmacokinetics of this new dosing regimen in real-life settings. Methods We prospectively recruited 30 consecutive (17 with body w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…14 Real-world data remain important to assess performance of a drug under non-ideal conditions in clinical practice, when treatment cannot be limited to patients fulfilling narrow inclusion criteria, 15 with only about one in four real-life UC patients qualifying for participation in randomized controlled trials. 16 Some real-world data and post-marketing studies for golimumab in UC are available, 14,[17][18][19][20][21][22][23][24][25][26] these generally confirmed effectiveness and safety of golimumab treatment. In some of these studies, clinical response and remission, 18,22,23,25 and persistence rates, 17 were higher in anti-TNF naïve patients compared with non-naïve patients.…”
Section: Effectiveness Of Golimumab In Patients With Ulcerative Colit...mentioning
confidence: 89%
“…14 Real-world data remain important to assess performance of a drug under non-ideal conditions in clinical practice, when treatment cannot be limited to patients fulfilling narrow inclusion criteria, 15 with only about one in four real-life UC patients qualifying for participation in randomized controlled trials. 16 Some real-world data and post-marketing studies for golimumab in UC are available, 14,[17][18][19][20][21][22][23][24][25][26] these generally confirmed effectiveness and safety of golimumab treatment. In some of these studies, clinical response and remission, 18,22,23,25 and persistence rates, 17 were higher in anti-TNF naïve patients compared with non-naïve patients.…”
Section: Effectiveness Of Golimumab In Patients With Ulcerative Colit...mentioning
confidence: 89%
“… 35 Dose escalation by interval shortening alone was reported in 31 studies ( Supplementary Table 6 ); 21–23 , 26–28 , 31 , 32 , 34 , 36–38 , 41 , 44 , 46 , 47 , 49–52 , 55 , 58 , 59 , 64–68 , 70 , 71 , 74 , 75 this most commonly occurred with IFX (from 5 mg/kg every 8 to 4 weeks) and ADA (from 40 mg every 2 weeks to once weekly).
Figure 2 Proportion of patients treated with dose escalation due to loss of response 31 , 44 , 46 , 63 , 66–68 , 75 , 76 or any reason. 22–29 , 32 , 34 , 35 , 37 , 38 , 40–42 , 45 , 47–52 , 55 , 57–62 , 64 , 65 , 69 , 71 , 72 , 74 Studies originating in multiple countries and including multiple anti-TNF therapies were counted more than once, giving a total number of references higher than the 48 publications found.
…”
Section: Resultsmentioning
confidence: 99%
“…1,2 However, there are only limited data regarding golimumab and the ideal drug concentration threshold to target when applying TDM in clinical practice. [3][4][5][6][7] Taxonera et al performed a multicenter, cross-sectional, cohort study in 52 patients with ulcerative colitis (UC) treated with golimumab and found positive associations between maintenance golimumab trough concentrations (GTCs) with several stringent sole and composite outcomes, such as clinical remission (Partial Mayo Score…”
Section: N V I T E D E D I T O R I a Lmentioning
confidence: 99%
“…These results are in line with previous studies showing that higher golimumab concentrations are associated with higher rates of favourable therapeutic outcomes. [3][4][5][6][7] A post hoc analysis of the phase 2/3 PURSUIT randomised controlled trials (RCTs) identified golimumab concentrations thresholds of 0.9 μg/ml at week 28 and 1.4 μg/ml at week 44 with clinical remission at week 54. 4 This study has several inherent limitations.…”
Section: N V I T E D E D I T O R I a Lmentioning
confidence: 99%
See 1 more Smart Citation